Assessment of renewable energy sources to generate electricity for remote areas, South Iraq - Ali Hadi Kother; Zaidoon Waleed AL-Shammari Waleed Jawad; Safaa Kother; Ihsan Ahmed Taha; Hussam Almukhtar; Muhammad Mokhzaini Azizan; Ahmad Shukri Fazil Rahman; Khairunnisa Hasikin (Institute of Advanced Engineering and Science, 2022)
With the rising need for utilizing renewable energy instead of traditional energies in electricity generation across the world, a broad assessment of these energies' performance is required to make the most of them everywhere. This paper looks at the techno-economics of renewable energy resources for a distant health clinic in a rural location of southern Iraq. Cost, dependability, and availability are the parameters that were considered in this study, which took into consider the power load in this scenario. Because of its efficacy, the particle swarm optimization (PSO) technique was chosen for the suggested study. Results showed that the respective optimal values for number of photovoltaics (NPV) equal to (10), number of wind turbines (NWT) equal to (5), and number of batteries (NBT) of (33), cost of energy (COE) of (0.518 US/kWh), loss power supply probability (LPSP) of (0.073%), reliability (REL) of (99.927%) and renewable factors (RF) of (100%) with (66 %) solar energy penetration, and (34%) wind energy penetration. Finally, it was discovered that implementing a hybrid renewable energy system (HRES) is an effective way to address the electrical demands of remote rural regions in Iraq and other developing countries with similar climates.